2020
DOI: 10.21203/rs.3.rs-22189/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute effect of green tea catechins on uric acid metabolism after alcohol ingestion in Japanese men

Abstract: Objective: Alcohol consumption is associated with hyperuricemia and gout. Previous studies have indicated a role for green tea catechins in uric acid (UA) metabolism. This study aimed to elucidate the acute effect of green tea catechins in terms of enhancing urinary excretion of UA and xanthine/hypoxanthine (Xa/HX; UA precursors) after alcohol ingestion.Methods: In a randomized crossover study, ten healthy Japanese subjects consumed test meals, including a Japanese distilled spirit (Shōchū) with water (SW) or … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…For example, Wu et al (2020) reviewed the role of catechins in the disorders of uric acid metabolism and found that catechins regulated the expression of uric acid transporter proteins, ATP-binding cassette subfamily G member (ABCG) 2, URAT1, OAT1/3, and GLUT9 to balance uric acid secretion and reabsorption through the kidneys and intestine, thus lowering the uric acid level. Kawakami et al (2021) found that catechins affected the activity of XO and promoted the excretion of uric acid, xanthine, and hypopurine in Japanese men. As one of the main active ingredients of tea, EGCG is one of the most intensively studied flavanols.…”
Section: In Vivo Animal Experimental Analysis Of Flavanolsmentioning
confidence: 97%
“…For example, Wu et al (2020) reviewed the role of catechins in the disorders of uric acid metabolism and found that catechins regulated the expression of uric acid transporter proteins, ATP-binding cassette subfamily G member (ABCG) 2, URAT1, OAT1/3, and GLUT9 to balance uric acid secretion and reabsorption through the kidneys and intestine, thus lowering the uric acid level. Kawakami et al (2021) found that catechins affected the activity of XO and promoted the excretion of uric acid, xanthine, and hypopurine in Japanese men. As one of the main active ingredients of tea, EGCG is one of the most intensively studied flavanols.…”
Section: In Vivo Animal Experimental Analysis Of Flavanolsmentioning
confidence: 97%